A role for divalent metal transporter (DMT1) in mitochondrial uptake of iron and manganese - Natascha A. Wolff (Nature Portfolio, 2018)
Abstract Much of iron and manganese metabolism occurs in mitochondria. Uptake of redox-active iron must be tightly controlled, but little is known about how metal ions enter mitochondria. Recently, we established that the divalent metal transporter 1 (DMT1) is present in the outer mitochondrial membrane (OMM). Therefore we asked if it mediates Fe2+ and Mn2+ influx. Mitochondria were isolated from HEK293 cells permanently transfected with inducible rat DMT1 isoform 1 A/+IRE (HEK293-rDMT1). Fe2+-induced quenching of the dye PhenGreen™SK (PGSK) occurred in two phases, one of which reflected OMM DMT1 with stronger Fe2+ uptake after DMT1 overexpression. DMT1-specific quenching showed an apparent affinity of ~1.5 µM for Fe2+and was blocked by the DMT1 inhibitor CISMBI. Fe2+ influx reflected an imposed proton gradient, a response that was also observed in purified rat kidney cortex (rKC) mitochondria. Non-heme Fe accumulation assayed by ICPOES and stable 57Fe isotope incorporation by ICPMS were increased in HEK293-rDMT1 mitochondria. HEK293-rDMT1 mitochondria displayed higher 59Fe2+ and 54Mn2+ uptake relative to controls with 54Mn2+ uptake blocked by the DMT1 inhibitor XEN602. Such transport was defective in rKC mitochondria with the Belgrade (G185R) mutation. Thus, these results support a role for DMT1 in mitochondrial Fe2+ and Mn2+ acquisition.